(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Types of historical and archeological monuments in Karakalpakstan, history of arrival in Jampiqkala, social and economic development of shakar, new constructions of shakar on the island of the 9th-11th and 12th-14th centuries.